Study of Serum Electrolyte Levels in Type 2 Diabetes Mellitus - Siddiqui, A. M.; Choudhary, Swati K. (International Journal of Innovative Research in Medical Science, 2019)
Introduction: The incidence of diabetes mellitus is increasing rapidly with interference in electrolytes sodium (Na+), potassium (K+) and chloride (Cl-). The prevalence of diabetes mellitus is rapidly rising all over the globe at an alarming rate. Objective: Study of serum electrolyte levels in type 2 Diabetes Mellitus. Material and methods: Total of 100 subjects were included in the study, out of which two groups were formed; 50 type 2 diabetes mellitus patients and 50 controls. Centrifuged serum was analyzed for estimation of Na+, K+ and Cl- level by the Accustar auto analyzer. Results: In type 2 diabetes mellitus serum Na+ level was observed significantly decreased while Cl- and K+ levels were increased. Both the electrolytes (Na+ Cl-) differ significantly in diabetes and control group. Conclusion: Electrolyte metabolism is disturbed in type 2 diabetes mellitus and proper glycemic control and evaluation of electrolyte levels can reduce the fatalities associated with electrolyte derangement in type 2 diabetes mellitus.